2021
DOI: 10.1101/2021.05.11.21257057
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Family responsibilities and mental health of kindergarten educators during the first COVID-19 pandemic lockdown in Ontario, Canada

Abstract: The present cross-sectional study, conducted during the first wave of the COVID-19 pandemic in Ontario, Canada, addressed the association between family responsibilities and mental health (depression and anxiety) among kindergarten educators. Participants comprised 1,790 (97.9% female) kindergarten educators (73.6% kindergarten teachers; 26.4% early childhood educators) across Ontario. Results revealed that educators were more likely to report moderate levels of depressive symptoms if they had the responsibili… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 44 publications
(34 reference statements)
0
7
0
Order By: Relevance
“…A study by Spadafora et al [ 67 ] examined the relationship between kindergarten teachers’ mental health and their care for children and adolescents and indicated that family responsibilities affect their mental health. Since our study did not examine the family composition, future research should examine the effects of family composition and family relationships.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Spadafora et al [ 67 ] examined the relationship between kindergarten teachers’ mental health and their care for children and adolescents and indicated that family responsibilities affect their mental health. Since our study did not examine the family composition, future research should examine the effects of family composition and family relationships.…”
Section: Discussionmentioning
confidence: 99%
“…Identify the trend of research on anxiety and depression among teachers according to the year of publication approach and national context. Ratanasiripong et al, 2021;Santamaría et al, 2021;Wong et al, 2021;Wakui et al, 2021;Yoo et al, 2021;Bete et al, 2022;Gawrych et al, 2022;Lizana et al, 2022;Spadafora et al, 2022). 4 shows 5 sub-factors from work that lead to anxiety and depression of a teacher.…”
Section: Findings Findings Based On First Research Objectivementioning
confidence: 99%
“…Therefore, an abundance is tasks accumulated by teachers leads them to be constant under pressure from many parties ( Furthermore, the subfactor of teaching knowledge is also closely related to the teacher's tendency to anxiety and depression. This is because teachers who are incompetent in pedagogy and content knowledge will have low self-esteem making them to be living in fear that causes anxiety and depression in themselves (Desouky & Allam, 2017;Ramirez et al, 2018;Alvites et al, 2019;Dizon-Ross et al, 2019;Ganley et al, 2019;Oguzhan et al, 2019;Thomas & Sari, 2019;Othman & Sivasubramaniam, 2019;Li et al, 2020;Syuhada & Retnawati 2020;Bete et al, 2020;Genoud & Waroux, 2021;Pressley et al, 2021;Wakui et al, 2021;Gawrych et al, 2022;Spadafora et al, 2022).…”
Section: Occupational Factormentioning
confidence: 99%
See 2 more Smart Citations